2016
DOI: 10.1172/jci.insight.89081
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cell transfer ameliorates lymphedema and promotes lymphatic vessel function

Abstract: Secondary lymphedema is a common postcancer treatment complication, but the underlying pathological processes are poorly understood and no curative treatment exists. To investigate lymphedema pathomechanisms, a top-down approach was applied, using genomic data and validating the role of a single target. RNA sequencing of lymphedematous mouse skin indicated upregulation of many T cell-related networks, and indeed depletion of CD4 cells attenuated lymphedema. The significant upregulation of Foxp3, a transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 46 publications
5
74
0
Order By: Relevance
“…Indeed, the depletion of Treg cells exacerbates edema and fibrosis and is associated with increased infiltration of immune cells with a mixed Th1/Th2 cytokine profile (Gousopoulos et al, 2016a). Conversely, expansion of T regulatory cells significantly reduced lymphedema development by attenuating the tissue inflammation in lymphedema (Gousopoulos et al, 2016a). However, these cells may also participate to the local immune suppression observed in lymphedema, which is consistent with the recurrence of soft tissue infections observed in this disease (Sharkey et al, 2017;Garcia Nores et al, 2018).…”
Section: Role Of Inflammationsupporting
confidence: 54%
See 2 more Smart Citations
“…Indeed, the depletion of Treg cells exacerbates edema and fibrosis and is associated with increased infiltration of immune cells with a mixed Th1/Th2 cytokine profile (Gousopoulos et al, 2016a). Conversely, expansion of T regulatory cells significantly reduced lymphedema development by attenuating the tissue inflammation in lymphedema (Gousopoulos et al, 2016a). However, these cells may also participate to the local immune suppression observed in lymphedema, which is consistent with the recurrence of soft tissue infections observed in this disease (Sharkey et al, 2017;Garcia Nores et al, 2018).…”
Section: Role Of Inflammationsupporting
confidence: 54%
“…Studies by the group of B. J. Mehrara and M. Detmar showed in clinical and experimental lymphedema that the majority of the cells that accumulate chronically in lymphedematous tissues are CD4 + T cells and that they contribute to the pathological changes including fibrosis (Avraham et al, 2010(Avraham et al, , 2013Zampell et al, 2012c;Savetsky et al, 2014;Gousopoulos et al, 2016b). Further phenotypic characterization of the infiltrating CD4 + T cells revealed that there is a mix of Th1, Th2, and regulatory T cells (Avraham et al, 2013;Gousopoulos et al, 2016a). Notably, the blockade of Th2 differentiation but not Th1 differentiation was effective in preventing the development of lymphedema, and in established cases, treating it (Avraham et al, 2013;Ly et al, 2019).…”
Section: Role Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cx43 is known to be expressed by mesenchymal stem cells, which can affect lymphangiogenesis (Valiunas et al, 2004; Buttler et al, 2013; Maertens et al, 2014), as well as macrophages and lymphocytes (Glass et al, 2015), which have been implicated in pathological lymphangiogenesis (Betterman and Harvey, 2016). In addition, Cx43 expression in thymic regulatory T cell precursors enhances the production of Foxp3 + regulatory T cells (Kuczma et al 2011), a population of cells which were recently shown to modulate lymphedema and promote lymphatic vessel function (Gousopoulos et al, 2016). During development, lymphangiogenesis in the diaphragm is regulated by macrophages, which are closely associated with the sprouting tips of lymphatic vessels (Ochsenbein et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The lymphatic vasculature is critical to immunity with one of its major roles being the trafficking of immune cells . High VEGF‐C expression in experimental mouse models has previously been found to promote lymphatic vessel enlargement with lymphatic endothelial cell proliferation . Recently, several studies have found that dilated lymphatic vessels exhibit impaired transport capacity, making immune cells difficult to transport into the tumor.…”
Section: Discussionmentioning
confidence: 99%